Chemoselective Hydrogenation of Functionalized Nitroarenes using Supported Mo Promoted Pt Nanoparticles. Issue 2 (23rd November 2012) - Boymans, Evert; Boland, Susan; Witte, Peter T.; Müller, Christian; Vogt, Dieter
<x xml:space="preserve">Abstract</x> Positive discrimination: Supported MoVI promoted Pt nanoparticles (c‐Pt+Mo/C) are successfully applied as catalysts in the chemoselective hydrogenation of functionalized nitroarenes. Mild conditions (30 °C, 4 bar H2, EtOH) prove sufficient for complete reduction to the corresponding anilines, leaving other functional groups untouched. Turnover numbers of at least 20 000 show that this catalyst is very tolerant to halogen‐containing aromatics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>